Endovascular transluminal stent grafting: Treatment of choice for post lumbar spine surgery iliac arterio‐venous fistulae. Issue 6 (9th November 2013) - Rohit, Manoj Kumar; Gupta, Ankur; Khandelwal, N.
Abstract : Iliac vessels are prone to injury during lumbar spine surgery due to their proximity to the lumbar spine. Arterio‐venous fistula formation during lumbar spine surgery is an uncommon complication and can present as an asymptomatic incidental finding to rapidly deteriorating hemodynamics leading to cardiopulmonary collapse. We have reported three patients who had symptomatic iliac arterio‐venous fistula detected soon after lumbar spine surgery. All these patients were successfully treated by endovascular transluminal stent grafting. © 2013 Wiley Periodicals, Inc.